If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x + -22) = -121 Reorder the terms: X(-22 + x) = -121 (-22 * X + x * X) = -121 (-22X + xX) = -121 Solving -22X + xX = -121 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: 121 + -22X + xX = -121 + 121 Combine like terms: -121 + 121 = 0 121 + -22X + xX = 0 The solution to this equation could not be determined.
| 1-5x=13-9x | | -13(V-6)=-5V+2(5V+12) | | Y^3=36y | | 2x+22=9x-62 | | 2x-(x+4)+16=3(x-3)-3 | | 2-4(x+2)=7x-17 | | -5-8p=-3p | | -28+5=3x+2-2x | | 27-g=2g+12 | | 14-3(x-1)=5 | | 6(7e+5f-3f)= | | 3x+21=12x-51 | | 36-5x=4x+20 | | 11y+12=5y+66 | | x+2=22 | | 5(2z+1)=5(z-5) | | -7(5x-1)+9=-35x+16 | | 7x-3x+6=x-9+15 | | -1+-6= | | 5(x+6)-3=29-6x-2+11x | | 3x^2-8x+2=0 | | 3x+9=10x-26 | | 3x-3=11x-35 | | 7x+3=3x+51 | | -1+9(x-4)=16x+6-7x | | -27+x=-17 | | 2x^2-3x-8=0 | | 12.3x=28.29 | | 3x+12=78 | | -27+x=-27 | | 38-3x=6x+17 | | (-3w^2+w-4)+(5w^2+7w+2)= |